TAMI-26. INVESTIGATING TUMOR MICROENVIRONMENT METABOLIC DEPENDENCIES IN GLIOBLASTOMA. (12th November 2021) - Minami, Jenna; Bayley, Nicholas; Tse, Christopher; Morrow, Danielle; Zhu, Henan; Yong, William; Liau, Linda; Cloughesy, Timothy; Graeber, Thomas; Nathanson, David
Abstract: Metabolic reprogramming is a hallmark of cancer. Malignant cells must acquire metabolic adaptations in response to a multitude of intrinsic and extrinsic factors to fuel neoplastic progression. Mutations or changes in metabolic gene expression can impose nutrient dependencies in tumors, and even in the absence of metabolic defects, cancer cells can become auxotrophic for particular nutrients or metabolic byproducts generated by other cells in the tumor microenvironment (TME). Altered metabolism in GBM is becoming an increasingly promising area of research to identify novel therapeutic targets and biomarkers, as metabolic rewiring can occur across numerous genotypes. The unique features of the brain TME pose a difficult challenge when studying GBM and other primary brain cancers – currently, the availability of nutrients in the brain, as well as how they influence or are influenced by tumor metabolism, are not well understood. Our group has identified a subgroup of gliomas, hereafter termed TME-dependent, which can only form tumors in the brain TME. While genetically heterogeneous, these tumors share transcriptional identities linked to oligodendrocyte precursor cell (OPC) and neuronal lineages. Systematic molecular profiling of over 75 patient tumors and their matched cell culture and brain orthotopic xenograft derived models revealed that TME-dependent tumors display lipid metabolic signatures linked to signaling and interactions with surrounding neurons and glial cells. Collectively, these data emphasize the metabolic heterogeneity within GBM, and reveal a subset of gliomas that lack metabolic plasticity in fatty acid biosynthetic programs, indicating a potential brain-microenvironment specific metabolic dependency linked to transcriptional identity that can be targeted for therapy.